Africa’s Economic Development, Nutrition, and Health - Babatunde Omilola; N’doh A. Sanogo (Public Health, 2024)
The term “well-nourished populations” is the opposite of malnutrition. According to the World Health Organization (WHO), mal nutrition refers to deficiencies, excesses or imbalance in a person’s intake of energy and/or nutrients.